Breeding larvae Russian Acipenser baeri and Siberian sturgeon Acipenser guldenstadti installations recirculation (Eurasian Journal of Ecology, 2016)
The article gives the results of the growth rate of larvae Russian and Siberian sturgeon farmed in RAS Almatiskoy area. The results showed increased growth rate of Siberian sturgeon compared to Russian sturgeon.
Keywords: Russian sturgeon; Siberian sturgeon; larva; growth rate; feed; RAS